(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Freedom of expression is one of the essential elements of modern democratic states’ standard for basic civil rights and freedoms. It is most often guaranteed in the constitutions as well as in ratified acts of European and international law. Still, freedom of speech is not absolute, meaning in certain situations it may be restricted to protect another legal value. A prominent example is hate speech, as a means of spreading hatred, hostility and violence towards a person or a particular group. It is not a closed book but widely regarded as a significant violation of human rights. While there is no doubt it constitutes a freedom of speech abuse, the issue of its sanctioning falls within controversial and multifaceted challenges in terms of legislative regulation. The purpose of this article is to compare Polish and Croatian legal systems on this issue. The research will be based on the comparative method, designed to detect similarities, differences and possible patterns in the subject area of the study and to determine the variables affecting the evaluation of current and developed policies in the area of hate speech responsibility and sanctioning. The specific solutions contained in the national constitutional positions, criminal law, misdemeanor law, related body of doctrine and selected case law show a certain diversity of approaches. It can be said that in the area under consideration we are dealing with variants of the same general concept. The results of the conducted analyses will form the basis for further research in the field of amendment of regulations on the punishment of hate speech in the Polish and Croatian legal systems.